Dysregulated Hypothalamic–Pituitary–Adrenal Axis Is Associated With Increased Inflammation and Worse Outcomes After Ischemic Stroke in Diabetic Mice - Kim, Sehee; Park, Eun S.; Chen, Peng R.; Kim, Eunhee (Frontiers in Immunology, 2022)
Diabetic patients have larger infarcts, worse neurological deficits, and higher mortality rate after an ischemic stroke. Evidence shows that in diabetes, the hypothalamic–pituitary–adrenal (HPA) axis was dysregulated and levels of cortisol increased. Based on the role of the HPA axis in immunity, we hypothesized that diabetes-dysregulated stress response exacerbates stroke outcomes via regulation of inflammation. To test this hypothesis, we assessed the regulation of the HPA axis in diabetic mice before and after stroke and determined its relevance in the regulation of post-stroke injury and inflammation. Diabetes was induced in C57BL/6 mice by feeding a high-fat diet and intraperitoneal injection of streptozotocin (STZ), and then the mice were subjected to 30 min of middle cerebral artery occlusion (MCAO). Infarct volume and neurological scores were measured in the ischemic mice. The inflammatory cytokine and chemokine levels were also determined in the ischemic brain. To assess the effect of diabetes on the stroke-modulated HPA axis, we measured the expression of components in the HPA axis including corticotropin-releasing hormone (CRH) in the hypothalamus, proopiomelanocortin (POMC) in the pituitary, and plasma adrenocorticotropic hormone (ACTH) and corticosterone. Diabetic mice had larger infarcts and worse neurological scores after stroke. The exacerbated stroke outcomes in diabetic mice were accompanied by the upregulated expression of inflammatory factors (including IL-1β, TNF-α, IL-6, CCR2, and MCP-1) in the ischemic brain. We also confirmed increased levels of hypothalamic CRH, pituitary POMC, and plasma corticosterone in diabetic mice before and after stroke, suggesting the hyper-activated HPA axis in diabetic conditions. Finally, we confirmed that post-stroke treatment of metyrapone (an inhibitor of glucocorticoid synthesis) reduced IL-6 expression and the infarct size in the ischemic brain of diabetic mice. These results elucidate the mechanisms in which the HPA axis in diabetes exacerbates ischemic stroke. Maintaining an optimal level of the stress response by regulating the HPA axis may be an effective approach to improving stroke outcomes in patients with diabetes.